Effect of long-term omega 3 polyunsaturated fatty acid supplementation with or without multidomain intervention on cognitive function in elderly adults with memory complaints (MAPT): a randomised, placebo-controlled trial. Issue 5 (May 2017) - Andrieu, Sandrine; Guyonnet, Sophie; Coley, Nicola; Cantet, Christelle; Bonnefoy, Marc; Bordes, Serge; Bories, Lawrence; Cufi, Marie-Noëlle; Dantoine, Thierry; Dartigues, Jean-François; Desclaux, Françoise; Gabelle, Audrey; et al.
Summary: Background: No large trials have been done to investigate the efficacy of an intervention combining a specific compound and several lifestyle interventions compared with placebo for the prevention of cognitive decline. We tested the effect of omega 3 polyunsaturated fatty acid supplementation and a multidomain intervention (physical activity, cognitive training, and nutritional advice), alone or in combination, compared with placebo, on cognitive decline. Methods: The Multidomain Alzheimer Preventive Trial was a 3-year, multicentre, randomised, placebo-controlled superiority trial with four parallel groups at 13 memory centres in France and Monaco. Participants were non-demented, aged 70 years or older, and community-dwelling, and had either relayed a spontaneous memory complaint to their physician, limitations in one instrumental activity of daily living, or slow gait speed. They were randomly assigned (1:1:1:1) to either the multidomain intervention (43 group sessions integrating cognitive training, physical activity, and nutrition, and three preventive consultations) plus omega 3 polyunsaturated fatty acids (ie, two capsules a day providing a total daily dose of 800 mg docosahexaenoic acid and 225 mg eicosapentaenoic acid), the multidomain intervention plus placebo, omega 3 polyunsaturated fatty acids alone, or placebo alone. A computer-generated randomisation procedure was used to stratify patients by centre. All participants and study staff were blinded to polyunsaturated fatty acid or placebo assignment, but were unblinded to the multidomain intervention component. Assessment of cognitive outcomes was done by independent neuropsychologists blinded to group assignment. The primary outcome was change from baseline to 36 months on a composite Z score combining four cognitive tests (free and total recall of the Free and Cued Selective Reminding test, ten Mini-Mental State Examination orientation items, Digit Symbol Substitution Test, and Category Naming Test) in the modified intention-to-treat population. The trial was registered withClinicalTrials.gov (NCT00672685 ). Findings: 1680 participants were enrolled and randomly allocated between May 30, 2008, and Feb 24, 2011. In the modified intention-to-treat population (n=1525), there were no significant differences in 3-year cognitive decline between any of the three intervention groups and the placebo group. Between-group differences compared with placebo were 0·093 (95% CI 0·001 to 0·184; adjusted p=0·142) for the combined intervention group, 0·079 (−0·012 to 0·170; 0·179) for the multidomain intervention plus placebo group, and 0·011 (−0·081 to 0·103; 0·812) for the omega 3 polyunsaturated fatty acids group. 146 (36%) participants in the multidomain plus polyunsaturated fatty acids group, 142 (34%) in the multidomain plus placebo group, 134 (33%) in the polyunsaturated fatty acids group, and 133 (32%) in the placebo group had at least one serious emerging adverse event. Four treatment-related deaths were recorded (two in the multidomain plus placebo group and two in the placebo group). The interventions did not raise any safety concerns and there were no differences between groups in serious or other adverse events. Interpretation: The multidomain intervention and polyunsaturated fatty acids, either alone or in combination, had no significant effects on cognitive decline over 3 years in elderly people with memory complaints. An effective multidomain intervention strategy to prevent or delay cognitive impairment and the target population remain to be determined, particularly in real-world settings. Funding: French Ministry of Health, Pierre Fabre Research Institute, Gerontopole, Exhonit Therapeutics, Avid Radiopharmaceuticals.